Strategies to Reduce The Multifetal Pregnancy in Infertility Treatment - Suphakde Julavijitphong (The Royal Thai College of Obstetricians and Gynaecologists, 2010)
During the past three decades, the modern infertility treatment has been worldwide successfully achieved to help tons of infertile couples to have their own babies. Since the birth of Louise Brown, the world's first in vitro fertilization (IVF) baby in 1978, there have been more than three million babies born from this technology all over the world(1). It is estimated that about 1% of the baby born are from the assisted reproductive technology (ART). Coming up with the good success of the ART in the infertility treatment is the explosive of the huge multiple pregnancy rate compared to the natural conception, of which around 10% are high- order multiple pregnancy (HOMP)(2,3). Recent report from European Society of Human Reproduction and Embryology (ESHRE) (generated from 32 European countries), the multiple pregnancy rate from ART has been consistently high at the figure of over 20% of the live birth(4). In Thailand, The Royal Thai College of Obstetricians and Gynaecologists, reported that the twin pregnancy rate was 19.7% and the triplet and quadruplet were 1.9% and 0.5 % respectively during the past six years.